The effect of a low‐dose naloxone infusion on the incidence of respiratory depression after intrathecal morphine administration for major open hepatobiliary surgery: a randomised controlled trial. (2nd December 2019) - Cosgrave, D.; Vencken, S.; Galligan, M.; McGuinness, S.; Soukhin, E.; McMullan, V.; Nair, S.; Puttappa, A.; Boylan, J.; Hussain, R.; Conlon, N.; Doran, P.; et al.
Summary: Intrathecal morphine is an analgesic option for major hepatopancreaticobiliary procedures but is associated with a risk of respiratory depression. We hypothesised that a postoperative low‐dose naloxone infusion would reduce the incidence of respiratory depression without an increase in pain scores. Patients scheduled for major open hepatopancreaticobiliary surgery and who were receiving 10 μg.kg −1 intrathecal morphine were eligible for inclusion. Patients were allocated randomly to receive a postoperative infusion of naloxone 5 μg.kg −1 .h −1 (naloxone group) or saline at an identical infusion rate (control group) until the morning after surgery. Clinicians, nursing staff and patients were blinded to group allocation. The primary outcome measure was the incidence of respiratory depression (respiratory rate < 10 breaths.min −1 and/or oxygen saturation < 90%). Secondary outcome measures included: arterial partial pressure of carbon dioxide; pain score; requirement for supplemental analgesic; and incidence of nausea and vomiting, pruritus and sedation. In total, data from 95 patients (48 in the naloxone group and 47 in the control group) were analysed. The incidence of respiratory depression was lower in the naloxone group compared with the control group (10/48 vs. 21/47 patients, respectively; p = 0.037, relative risk 0.47 (95%CI 0.25–0.87). Maximum pain scores were greater for patients allocated to the naloxone group compared with control (median 5 (95%CI 4–6) vs. 4 (95%CI 2–4), respectively; p < 0.001). A low‐dose naloxone infusion decreases the incidence of respiratory depression following intrathecal morphine administration in patients having major hepatopancreaticobiliary surgery at the expense of a small increase in postoperative pain.